2018
DOI: 10.1186/s12885-018-4738-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antitumor and anti-angiogenic effects of metronomic Vinorelbine combined with Endostar on Lewis lung carcinoma

Abstract: BackgroundConventional chemotherapy is commonly used to treat non-small cell lung cancer (NSCLC) however it increases therapeutic resistance. In contrast, metronomic chemotherapy (MET) is based on frequent drug administration at lower doses, resulting in inhibition of neovascularization and induction of tumor dormancy. This study aims to evaluate the inhibitory effects, adverse events, and potential mechanisms of MET Vinorelbine (NVB) combined with an angiogenesis inhibitor (Endostar).MethodsCirculating endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Metronomic chemotherapy comprises the frequent administration of drugs at lower doses to inhibit neovascularization and induce tumor dormancy. The study was performed on a xenograft model of human lung cancer and it proved the efficiency of this strategy for anti-tumoral purposes, as it led to enhanced anti-tumor and anti-angiogenic effects without causing toxicity compared with either agent alone [136]. Apatinib is another anti-angiogenic agent that was assessed for its efficacy and safety in combination with an oral etoposide for the treatment of platinum-resistant or platinum-refractory ovarian cancer.…”
Section: Novel Anti-angiogenic Strategies For Cancer Treatmentmentioning
confidence: 99%
“…Metronomic chemotherapy comprises the frequent administration of drugs at lower doses to inhibit neovascularization and induce tumor dormancy. The study was performed on a xenograft model of human lung cancer and it proved the efficiency of this strategy for anti-tumoral purposes, as it led to enhanced anti-tumor and anti-angiogenic effects without causing toxicity compared with either agent alone [136]. Apatinib is another anti-angiogenic agent that was assessed for its efficacy and safety in combination with an oral etoposide for the treatment of platinum-resistant or platinum-refractory ovarian cancer.…”
Section: Novel Anti-angiogenic Strategies For Cancer Treatmentmentioning
confidence: 99%
“…Also, Qin RS et al (2018) have successfully used metronomic therapy (low dose -high frequency) with Vinorelbine (NVB) administered with a known angiogenesis inhibitor, Endostar, to treat animal subjects with non-small cell lung cancer [35]. In the same study, they observed a significant decrease of HIF-1 as well as VEGF and CD31 associated with a decrease in tumour development as assessed by micro fluorine-18-deoxyglucose PET/computed tomography (18F-FDG PET/CT) [35]. However, the authors did not report a reduction in cancerassociated angiogenesis.…”
Section: B Hypoxia-inducible Factors (Hif)mentioning
confidence: 99%
“…Studies conducted in-vitro in human breast cancer cell line (MDA-MB-231) have revealed that analogues of the CJ-3k antagonist have an efficient anti-HIF activity suggesting that they might be effective as anticancer pharmacological agents [34]. Also, Qin RS et al (2018) have successfully used metronomic therapy (low dose -high frequency) with Vinorelbine (NVB) administered with a known angiogenesis inhibitor, Endostar, to treat animal subjects with non-small cell lung cancer [35]. In the same study, they observed a significant decrease of HIF-1 as well as VEGF and CD31 associated with a decrease in tumour development as assessed by micro fluorine-18-deoxyglucose PET/computed tomography (18F-FDG PET/CT) [35].…”
Section: B Hypoxia-inducible Factors (Hif)mentioning
confidence: 99%
See 2 more Smart Citations